2011
DOI: 10.3177/jnsv.57.326
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Vitamin E Metabolites in Rats after Oral Administration of Tocopherol or Tocotrienol

Abstract: SummaryWe previously found that 2,7,8-trimethyl-2(2 ′ -carboxyethyl)-6-hydroxychroman ( ␥ CEHC), a metabolite of the vitamin E isoforms ␥ -tocopherol or ␥ -tocotrienol, accumulated in the rat small intestine. The aim of this study was to evaluate tissue distribution of vitamin E metabolites. A single dose of ␣ -tocopherol, ␥ -tocopherol or a tocotrienol mixture containing ␣ -and ␥ -tocotrienol was orally administered to rats. Total amounts of conjugated and unconjugated metabolites in the tissues were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(24 reference statements)
1
18
0
2
Order By: Relevance
“…CEHC is then conjugated with glucuronate in humans or with sulfate in rats and subsequently excreted in the urine. Vitamin E metabolites are found in the liver, kidneys, small intestine, and serum of rats after oral administration of tocopherol or tocotrienol [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEHC is then conjugated with glucuronate in humans or with sulfate in rats and subsequently excreted in the urine. Vitamin E metabolites are found in the liver, kidneys, small intestine, and serum of rats after oral administration of tocopherol or tocotrienol [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ketoconazole also increased c-tocopherol concentrations in rat tissues by inhibiting its catabolism to c-CEHC, suggesting that CYP-dependent catabolism of vitamin E is a critical determinant of its bioavailability. Some reports indicate that a-tocopherol enhances c-tocopherol catabolism to c-CEHC [35,36,39]. In contrast, dietary a-tocopherol does not affect urinary excretion of c-CEHC in rats fed a diet containing c-tocotrienol for 8 weeks [19].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is a chain-breaking antioxidant; it is able to repair oxidizing radicals directly, preventing the chain propagation step during lipid peroxidation [7]. In the vitamin E group, alpha-tocopherol (ATPH) and alpha-tocotrienol (ATTN) are suggested to have the highest biological activity [8,9]. However, the functions of tocotrienols have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, accumulation of ␣ -tocotrienol in various organs could be demonstrated when large quantities of ␣ -tocotrienol were administered by gavage for more than two years; when ␣ -tocotrienol administration was stopped and the diet was replaced with a vitamin E-defi cient diet, ␣ -tocotrienol depletion took less than two months, while loss of ␣ -tocopherol was negligible ( 117 ). Uchida et al ( 118,119 ) showed that ␣ -tocopherol stimulated the disappearance of non-␣ -tocopherol and increased CEHC production. It is likely that metabolism of the tocotrienols observed in rats led to its rapid disappearance, as faster turnover of tocotrienols has also been seen in humans ( 120 ).…”
Section: ␣ -Tocopherol and Non-␣ -Tocopherol Metabolismmentioning
confidence: 99%